Peran pemerintah desa dalam Pemberdayaan Kelompok Tani di Desa Sri Bintan Kecamatan Teluk Sebong Kabupaten Bintan Tahun 2022: The role of the village government in Impowerment of Farmer Group In Sri Bintan Village, Teluk Sebong District Bintan District In 2022 - Sugiarno, Adi; Nazaki; Satyagraha Adiputra, Yudhanto (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2024)
This research aims to determine the role of the Village Government in Empowering the Farmer Group community through 4 (four) role indicators, the role of the Village Government as Regulator, Dynamisator, Facilitator and the role of the Village Government as a Catalyst in empowering farmer groups in Sri Bintan Village, Teluk Sebong District, Bintan Regency. The method used is a qualitative descriptive method with 7 (seven) informants and using data collection techniques and tools in the form of observation, interviews and documentation. The results of the research show that the role of the Village Government in empowering farmer groups has been running but is not yet optimal. For the government's role as a regulator, there are already authorities and regulations for community empowerment, one of which is in developing farming communities to form farmer groups. Furthermore, the dynamist aspect for implementing the dynamator. The Village Government has carried out these activities but it is not yet in accordance with what the farming group community wants. Furthermore, in the facilitator aspect, the Village Government has also impl emented it by providing facilities for the farmer group community to use, but in its implementation not all farmer groups have experienced the services provided. Then, for the catalytic aspect, the Village Government has supported and given attention to farmer groups to be able to unite so that they can progress further because the potential of natural resources and human resources can be developed.